De quelques applications particulières de l’ordinateur : actuelles ou à venir - H., J. (Assurances, 1981)
Computer technology has been applied in varied and extraordinary fashions to nearly all the fields of human endeavour. In the article presented below, the author has tried to summarize rapidly the scope of such applications which extend from hospital services to aviation, from accounting services to the manufacturing and insurance industries to say nothing of the invaluable contributions made to space technology. This extraordinary working tool which we call the computer has indeed enabled man to explore the moon and neighbouring planets of our solar system through the use of very intricate and complex electronic systems commanded from Earth.